Some aspects of the intellectual property legislation development to expand access to biotechnology medicines - Olha Omelchenko (Теорія і практика інтелектуальної власності)
The article examines the legal aspects of intellectual property and their impact on access to biotechnology medicines, considering prospects for legislative reform. The author analyzes legal mechanisms for ensuring access to medicines and their implementation in national legislation. Key priorities and reform prospects in intellectual property and pharmaceutical legislation are identified, addressing the challenges of martial law, European integration commitments, and the need to eliminate barriers to the timely market entry of generics and biosimilars. Intellectual property rights are a valuable asset of companies developing biotechnology products, and proper protection of intellectual property rights provides incentives for research in the pharmaceutical industry. Ukraine remains an importer of certain biotechnology products, including innovative medicines and vaccines not produced domestically. However, the country possesses well-developed manufacturing facilities capable of supplying high-quality generics and biosimilars to the domestic market. Efforts are underway to harmonize national legislation with EU law. Currently, there is no comprehensive legislative approach to regulating the use of biotechnology methods. Given ongoing transformations in EU pharmaceutical and biotechnology legislation, similar changes are expected in Ukraine. At the same time, a clear and unified conceptual framework remains necessary. Amid Russia’s military aggression, ensuring access to innovative medicines for the treatment of incurable or difficult-to-treat diseases is of critical importance. To expand access to biotechnology products, attract investment in the pharmaceutical industry and the introduction of innovations, and stabilize the market — particularly for generics, which are well-developed in Ukraine — legislative changes should enhance the effectiveness of the compulsory licensing mechanism. Strengthening this mechanism would serve as a vital tool for responding to emergencies and crises while safeguarding national economic interests.